Analisis Model Pengembangan Kurikulum pada Jenjang MI/SD: Studi Kasus di SD Yayasan Pendidikan Nursyamsiani - Fadillah Fadillah; Yuliananda Yuliananda; Della Salsabila Jannah; Zunidar Zunidar (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to analyze the curriculum development model applied at the elementary school level using a case study at the Nursyamsiani Education Foundation Elementary School. Curriculum development is a crucial aspect of education delivery because it serves as a guideline for achieving learning objectives that align with student needs and current developments. This study employed a qualitative research method with a case study approach. Data were obtained through observation, interviews, and documentation conducted at the Nursyamsiani Education Foundation Elementary School. The results indicate that the school implements an eclectic curriculum development approach, combining several curriculum development models: the Tyler, Taba, and Wheeler models. The Tyler model is evident in goal-oriented lesson planning, the Taba model is seen in active teacher involvement in the development of learning materials, and the Wheeler model is seen through continuous evaluation and improvement of the curriculum. The implementation of the Independent Curriculum also encourages more flexible, student-centered learning and supports the development of 21st-century character and competencies. Supporting factors for curriculum development include principal leadership, teacher competence, Teacher Working Group (KKG) activities, and professional training. Inhibiting factors include differences in teachers' understanding of the curriculum, time constraints, and the need to adapt to changing education policies. Overall, curriculum development at the Nursyamsiani Education Foundation Elementary School has been successful and has contributed to improving the quality of learning and education at the elementary school level.